Optimization Based on the Surface Plasmon Optical Properties of Adjustable Metal Nano-Microcavity System for Biosensing - Zhu, Jin; Yang, Yiye; Yin, Yanping; Yuan, Huining (Frontiers in Chemistry, 2021)
This paper mainly studies the plasma optical properties of the silver nanorod and gold film system with gap structure. During the experiment, the finite element analysis method and COMSOL Multiphysics are used for modeling and simulation. The study changes the thickness of the PE spacer layer between the silver nanorod and the gold film, the conditions of the incident light and the surrounding environment medium. Due to the anisotropic characteristics of silver nanorod, the microcavity system is extremely sensitive to the changes of internal and external conditions, and the system exhibits strong performance along the long axis of the nanorod. By an-alyzing the extinction spectrum of the nanoparticle and the electric field section diagrams at reso-nance peak, it is found that the plasma optical properties of the system greatly depend on the gap distance, and the surrounding electric field of the silver nanorod is confined in the gap. Both ends of the nanorod and the gap are distributed with high concentrations of hot spots, which reflects the strong hybridization of multiple resonance modes. Under certain excitation conditions, the plasma hybridization behavior will produce a multi-pole mode, and the surface electric field distribution of the nanorod reflects the spatial directionality. In addition, the system is also highly sensitive to the environmental media, which will cause significant changes in its optical properties. The plas-ma microcavity system with silver nanorod and gold film studied in this paper can be used to de-velop high-sensitivity biosensors, which has great value in the field of biomedical detection.